2020
DOI: 10.3390/ijms21062123
|View full text |Cite
|
Sign up to set email alerts
|

Brain Sex Differences Related to Gender Identity Development: Genes or Hormones?

Abstract: The complex process of sexual differentiation is known to be influenced by biological and environmental determinants. The present review has the aim of summarizing the most relevant studies on the biological basis of sexual development, and in particular, it focuses on the impact of sex hormones and genetic background on the development of sexual differentiation and gender identity. The authors conducted a search of published studies on Medline (from January 1948 to December 2019). The evidence suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 115 publications
0
45
1
4
Order By: Relevance
“…Indeed, hormonal influences not only affect internal and external genital development and differentiation; the embryo's brain has also been shown to differentiate sexually [12][13][14], perhaps through control mechanisms similar to those developed by the external genitalia [15]. On the other hand, it is also possible that the induction of the central nervous system (CNS) by hormones affects the patterns of hormonal secretion and, consequently, sexual behavior in adults [16][17][18][19][20]. Thus, the sex of an individual and their sexual expression, i.e., homoor heterosexual, must be considered the result of all influences that the individual receives, both before and after birth [8].…”
Section: Determination and Differentiation Of The Human Sexmentioning
confidence: 99%
“…Indeed, hormonal influences not only affect internal and external genital development and differentiation; the embryo's brain has also been shown to differentiate sexually [12][13][14], perhaps through control mechanisms similar to those developed by the external genitalia [15]. On the other hand, it is also possible that the induction of the central nervous system (CNS) by hormones affects the patterns of hormonal secretion and, consequently, sexual behavior in adults [16][17][18][19][20]. Thus, the sex of an individual and their sexual expression, i.e., homoor heterosexual, must be considered the result of all influences that the individual receives, both before and after birth [8].…”
Section: Determination and Differentiation Of The Human Sexmentioning
confidence: 99%
“…The potential impact of biologic and social/cultural factors in the etiology of GI/GD remains under debate. However, biology seems to play a major role [ 3 , 4 ]. In the last years, the idea of the sexual dimorphic brain as the anatomic substrate of psychosexual development has been more widely pursued and research has focused on the influence and shaping role of genes and gonadal hormones on sexual differentiation of the brain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the hippocampus (Ristori et al, 2020;Jones & Lopez, 2014;Sundermann et al, 2010), hypothalamus (Denley et al, 2018Mhaouty-Kodja et al, 2018;Xu et al, 2012;Sandremann et al, 2010), and amygdala (Mhaouty-Kodja et al, 2018;Jones & Lopez, 2014;Cooke et al, 2007) are repeatedly shown to be dimorphic in postmortem and in vivo imaging studies (Baldinger-Melich et al, 2020).…”
Section: The Limbic Systemmentioning
confidence: 99%
“…The dimorphic sexual brain is a substrate of psychosexual development, and the main determinants of cerebral differentiation are likely multimorphic. Genetic and hormonal influences have all been proposed (Ristori et al, 2020;Gliske, 2019;Legato, 2018). Further highlighting the possible developmental disconnect between sex and gender, sexual differentiation of the genitals takes place before sexual differentiation of the brain, making it possible that they are not always congruent (Tasopoulos, 2018;, Roselli, 2018).…”
Section: Lessons From Gender Incongruencementioning
confidence: 99%
See 1 more Smart Citation